Analysis of factors affecting the export performance in Cambodia: The ARDL bounds testing approach - El, Monineath (Journal of Management, Economics, and Industrial Organization, 2018)
This empirical study examines the factors affecting export performance in Cambodia through the period of 1993-2015. This study employed Autoregressive Distributed Lag (ARDL) model to investigate the long and short-run relationship among export and its determinant factors-inflation, real exchange rate, official development assistance, and trade liberalization. The study finds that INF obtains negative relationship with EX in both short and long run meanwhile TL has positive relationship with EX. But, RER has negative impact on the export performance in the short run only; ODA poses the significant positive relationship in the long run, vice versa. Unexpected positive relationship between crisis and export would be explain by insignificant impact of 1997 ASEAN financial crisis and the remaining growth of export during 2008 world economic crisis. The significant and negative coefficient of ECMt−1 indicates the relative speed of adjustment to achieve the long run equilibrium. This study suggests that government should prioritize to maintain inflation rate and real exchange rate, which negatively associate the export performance and export competitiveness of the country, at an optimum level. This study provides concrete evidence for policymakers in conducting the feasible policies to enhance and facilitate the trade liberalization in Cambodia